Captive maturation of the silver moony fish Monodactylus argenteus (Linnaeus, 1758) under laboratory conditions - Kumar, Prem; Arasu, A. R. T.; Kailasam, M.; Sundaray, J. K.; Biswas, G.; Subburaj, R.; Thiagarajan, G.; Elangeswaran, S. (Indian Journal of Fisheries, 2014)
The silver moony, Monodactylus argenteus is a highly priced euryhaline ornamental fish, which can survive well in freshwater, brackishwater as well as seawater. In the present investigation, an attempt was made to study the maturation of moony fish under controlled conditions. Sub-adults (mean weight 7.0 ± 0.45 g), caught from Ennore backwaters, were reared for a period of one year from January to d ecember 2010. Animals were fed ad libitum with frozen artemia biomass and formulated diet (32% crude protein, 8% lipid). Monthly sampling, through cannulation, was carried out to assess the maturity. Calculations of the biological parameters, like condition factor (K), gonado-somatic index (GSI) and histological analysis of gonad, were carried out from different size groups of animals to assess the maturity. Results of the present study showed that males attain sexual maturity at mean length of 13.16 ± 0.54 cm (mean weight 51.2 ± 0.33 g) and female of the same size was in maturing stage. The GSI was 0.62 in mature male and 0.72 in mature female. The value of GSI was found to increase with the advancement of maturaty in both the sexes (male 0.21 to 0.62; female 0.23 to 0.72), which was in accordance with histological observations